Combining multifaceted aspects of technology innovations through fuzzy clustering of multilayer networks - Roy Cerqueti; Giovanna Ferraro; Raffaele Mattera; Saverio Storani (PLoS ONE, 2025)
This study advances a novel multilayer network model to explore the connection between different aspects of Technological Innovation in European Union (EU) countries. We follow a fuzzy clustering approach and consider three variables: Research and Development (R&D), High-Tech Exports (HTE), and Human Resources in Science and Technology (HRST). We consider Eurostat data from 2018 to 2023. The variables form the layers, the EU countries are the nodes of the layers, and the weighted intra-layer links are assumed to increase with respect to the similarity of the countries in terms of the related variable. Interlayer connections are modeled probabilistically using a fuzzy clustering approach: two countries in different layers are strongly connected if they belong more probably to the same cluster in the related layers. The analysis offers insights into the patterns of EU countries in terms of Technological Innovation (TI) processes. The proposed framework allows its applicability to a wide set of real-world contexts.